Penerapan Model Cooperative Integrated Reading And Composition (CIRC) Dalam Pembelajaran Menulis Surat Pribadi Pada Peserta Didik Kelas Vii SMPN 1 Gunungwungkal Pati Tahun Ajaran 2022/2023 - Delima Eka Puspita; Suyoto Suyoto; Latif Anshori Kurniawan (CV. Alim's Publishing, 2024)
This research aims to determine the application of the Cooperative Integrated Reading and Composition (CIRC) model in learning to write personal letters for class VII students at SMPN 1 Gunungwungkal Pati. Based on the results of observations, there is a problem with class VII students at SMPN 1 Gunungwungkal Pati, namely that students still have difficulty using the right words and writing a message on personal letter writing material, because the learning model used by the teacher is not appropriate. This research uses mixed methods. Data collection was carried out using test and non-test techniques. The test technique is in the form of working on personal letter writing test questions, and the non-test technique is in the form of observation and questionnaires. Based on the research results, before implementing the Cooperative Integrated Reading and Composition (CIRC) model in learning to write personal letters, teachers still used Discovery Based Learning techniques for the learning process of writing personal letters and only used Indonesian language textbooks as learning support materials. The application of the Cooperative Integrated Reading and Composition (CIRC) model has proven that students are more active during learning. The (CIRC) model also makes students more enthusiastic and makes it easier for students to understand the material for writing personal letters.